329 ANTICHOLINERGIC BURDEN IN PEOPLE LIVING WITH DEMENTIA ATTENDING GERIATRIC MEDICINE AND PSYCHIATRY FOR OLDER PERSONS SERVICES. (25th October 2022) - Burke, S; Gibbons, O; Ahmed, M; Loughlin, E; Drumm, B; O'Sullivan, F; Hickey, P; O'Donnell, M; Dolan, C; McCarthy, G; O'Malley, G
Abstract: Background: Anticholinergic burden is associated with an increase in cognitive decline, delirium and confusion. We aimed to examine the Anticholinergic Cognitive Burden (ACB) of patients referred to local dementia services, and the prescribing of acetylcholinesterase inhibitors in patients with a significant anticholinergic burden. We also looked at frequency of prescribing of classes of some medications known to increase anticholinergic burden. Methods: A retrospective chart review was carried out of new referrals attending local Geriatric Medicine and/or Psychiatry For Older Persons outpatient services with a diagnosis of dementia between 2017 and 2018. Medications in use at the time of patient review were obtained. ACB was calculated using ACB score. Results were analysed descriptively. Results: 163 patients over 65 years old were included in this study, 94 (57.6%) were female. 30% (N = 49) had a significant anticholinergic burden (ACB >3). The mean ACB was 1.69 (Range 0 – 8). 38% of all patients (N = 63) were prescribed an acetylcholinesterase inhibitor, and of those, 20% (N = 13) had a significant anticholinergic burden. Polypharmacy (use of 5 medications or more) was evident with 76% (N = 124) patients. Regarding groups of medications known to increase ACB, 35.5% (N = 58) were prescribed antipsychotics and 18.4% (30) were prescribed benzodiazepines. Conclusion: There is a significant anticholinergic burden among people living with dementia attending the geriatric medicine and psychiatry of later life services. Some patients with a significant anticholinergic burden were being prescribed acetylcholinesterase inhibitors. This suggests acetylcholinesterase inhibitors may be prescribed without also discontinuing inappropriate medications that are contributing to the anticholinergic burden. We should look to further reduce the anticholinergic burden of patients attending the dementia services by avoiding these medications or using alternatives where available.